1988
DOI: 10.1002/mds.870030303
|View full text |Cite
|
Sign up to set email alerts
|

Writer's cramp: Not associated with anxiety

Abstract: Many authors have commented on an association between writer's cramp and anxiety and some view it as a form of anxiety disorder. This study describes 22 patients with writer's cramp who were recruited from a neurology clinic. Clinical examination found little evidence of generalized anxiety or of anxiety specific to the writing situation. Additionally, the subjects' scores on the Crown-Crisp Experiential Index, which contains several anxiety subscales, did not differ significantly from those of a matched norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 7 publications
(3 reference statements)
2
7
0
Order By: Relevance
“…The finding of anxiety in musicians with focal dystonia harmonizes with other reports of anxiety in patients with various forms of focal dystonia,7, 8, 13, 14 although findings in the literature are not unambiguous 9, 14. It has been suggested that reduced cortical inhibition may play a role in focal dystonia as well as in anxiety.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The finding of anxiety in musicians with focal dystonia harmonizes with other reports of anxiety in patients with various forms of focal dystonia,7, 8, 13, 14 although findings in the literature are not unambiguous 9, 14. It has been suggested that reduced cortical inhibition may play a role in focal dystonia as well as in anxiety.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have focused on psychological conditions in patients with other forms of dystonia. Depressive, anancastic, sensitive, and hysterical traits were observed in patients with writer's cramp,6 there have been contradicting reports about anxiety in patients with writer's cramp: anxiety was occasionally observed in patients with writer's cramp by Gibson7 and Cottraux and colleagues,8 whereas no higher levels of anxiety were seen in such patients compared to normal controls by Harrington and coworkers 9. Obsessive compulsive disorder has been reported in association with idiopathic focal dystonia10 as well as with myoclonus dystonia 11.…”
mentioning
confidence: 98%
“…That is non consistent to our study. In this present study maximum writer's cramp was associated with great deal of writing person like teacher, student, clerk which is consistent with Harrington's study 6 . In this present study there was no significant perfusion difference of basal ganglia between writer's cramp and non-writer's cramp group in the left side (P=0.851) during writing and also in the right side (P=0.671).…”
Section: Discussionsupporting
confidence: 91%
“…It is also unlikely that focal hand dystonia is due to an anxiety or neurotic disorder (9). We found no relationship between the medical history, personality scale scores, or patient test behavior and any of the characteristics of focal hand dystonia or motor performance as measured by finger dexterity or reaction times.…”
Section: Discussionmentioning
confidence: 91%